Anxiolytic and Antidepressant-Like Effects of the Aqueous Extract of Alafia multiflora Stem Barks in Rodents - Harquin Simplice Foyet; David Emery Tsala; Armand Abdou Bouba; Lucian Hritcu (Hindawi Limited, 2012)
The present study examined the anxiolytic and antidepressant effects of the aqueous extract of Alafia multiflora Stapf (AM) stem barks (150 and 300 mg/kg, 7 days administration) on rats and mice, using experimental paradigms of anxiety and depression. In the open field, the aqueous extract increased significantly the number of center square crossed and the time spent at the center of the field as well as the rearing time, while the grooming time was reduced significantly. In the elevated plus maze, the aqueous extract increased the time spent and the number of entries in the open arms. All these effects were also completely reversed by flumazenil, an antagonist of benzodiazepine receptors and pindolol a β-adrenoceptors blocker/5-HT 1A/1B receptor antagonist. The time spent in the light compartment, the latency time, and the number of the light-dark transitions increased significantly in the light/dark exploration test after the treatment with AM. The extract was able to reduce significantly the immobility time and increase swimming as well as climbing duration. Taken together, the present work evidenced anxiolytic effects of the aqueous extract of AM that might involve an action on benzodiazepine-type receptors and an antidepressant effect where noradrenergic mechanisms will probably play a role.